The archdiocesan secondary schools of Nueva Segovia a historical-descriptive study - Jaramillo, Elpidio F. 1919- (s.n.], 1967)
This study traced the history of the Archdiocese of Nueva Segovia and its secondary schools. This also determined their objectives and operations regarding the school curriculum, administration and supervision, extra curricular activities, and their possible educational contributions to the people of Ilocos Sur and La Union.